Assessment of Residual Moisture and Maintenance of Sterility in Surgical Instrument Sets after Sterilization. (20th May 2015) - Fayard, Camille; Lambert, Christophe; Guimier-Pingault, Catherine; Levast, Marion; Germi, Raphaelle
Abstract Good sterilization practices include discarding items containing residual moisture after steam sterilization. In this small laboratory study, however, the presence of residual water did not appear to compromise the sterility of surgical instruments in 2 commonly used types of packaging during routine storage after steam sterilization. Infect Control Hosp Epidemiol 2015;36(8):990–992